Studies of a Water-Only Cyclone with a Three-Stage Cone for Fine Coal Beneficiation. Issue 2 (4th March 2017) - Sun, Mingyang; Wei, Lubin; Cui, Guangwen
ABSTRACT: Separation tests on a high-sulfur-coal sample were carried out using a water-only cyclone (WOC) with a three-stage cone (also named a tri-cone water-only cyclone). The lower size limits of deashing and desulfurization were determined to be 0.098 mm and 0.045 mm, respectively. According to a float-and-sink analysis of various size fractions in the overflow and underflow, the Ecart probable ( Ep ) value as well as the separation density increased as the lower size fractions decreased. According to dynamic analysis, terminal hindered-settling velocities of spherical particles in the radial direction were obtained and an equation to estimate the lower removal size limits of heavy minerals was developed. With the help of numerical simulations of water–air two-phase flow fields in a tri-cone water-only cyclone (TWOC) and a conventional hydrocyclone, the role of the three-stage cone in the separation process was analyzed.